2016
DOI: 10.1007/s10067-016-3387-6
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of sleep quality and response to anti-tumor necrosis factor α therapy in rheumatoid arthritis patients

Abstract: Poor sleep quality (SQ) is increasingly recognized as giving rise to decreased quality of life, and raising pain perception. Our aim is to evaluate the SQ in rheumatoid arthritis (RA) patients treated with anti-tumor necrosis factor alpha (anti-TNF-α) therapy. This was a prospective observational and open-label study of RA patients. A total of 35 patients with RA were enrolled in this study. Of the 35 patients, 22 had high disease activity (DA), and 13 were in remission. High DA group was initiated an anti TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Appropriate dosage and timing of medications or medication change should be considered to keep associated sleep-disturbing effects at a minimum.In disorders characterized by immune dysregulations, immune-therapy may not only be used to improve disease activity, but also to directly improve sleep. As described in section II D2 , treatment of RA patients with IL-6 or TNF blockers improved sleep (196, 283, 535). Comparable effects of anti-TNF therapy on sleep were found in patients with IBD and ankylosing spondylitis (282, 527).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Appropriate dosage and timing of medications or medication change should be considered to keep associated sleep-disturbing effects at a minimum.In disorders characterized by immune dysregulations, immune-therapy may not only be used to improve disease activity, but also to directly improve sleep. As described in section II D2 , treatment of RA patients with IL-6 or TNF blockers improved sleep (196, 283, 535). Comparable effects of anti-TNF therapy on sleep were found in patients with IBD and ankylosing spondylitis (282, 527).…”
Section: Discussionmentioning
confidence: 88%
“…In a large cohort of over 8,000 patients from the National Data Bank of Rheumatic Diseases, self-reported sleep disturbances, including trouble falling asleep, trouble getting back to sleep, and not getting enough sleep to feel rested, did not differ between those who received anti-TNF therapy and those who did not (587). In contrast, treatment with anti-TNF therapy in RA patients with high disease activity resulted in an improvement of self-reported sleep quality, without affecting PSG-derived sleep parameters (283). However, at least three studies reported PSG-derived sleep improvements in response to anti-TNF therapy.…”
Section: The Sleep Response To Immune Activationmentioning
confidence: 99%
“…The PSQI is a legacy instrument that has been used to study prevalence of poor sleep and associated factors in a wide range of patients with rheumatologic diagnoses, including systemic lupus erythematosus (SLE) (30–32), RA (33–36), spondyloarthritides (37–39), systemic sclerosis (28,33), Sjögren syndrome (40,41), osteoarthritis (42–44), and fibromyalgia (45,46). It may not be able to detect well‐known disturbances of sleep that accompany aging (25).…”
Section: Pittsburgh Sleep Quality Indexmentioning
confidence: 99%
“…6 Similarly, selfreported sleep quality has by others been reported to be lower in RA, 17 and studies with objective measures of sleep showed more sleep fragmentation and more sleep apnea in RA patients compared to healthy controls. 16,18,19 Disturbed sleep has also been shown to covary with pain in patients with RA, 16 and similarly, apnea and nasal congestion in allergy might impair sleep. 9,16 Across a number of different patient and healthy populations, subjective sleep disturbances as well as long and short sleep durations, compared to normal, are associated with higher levels of interleukin (IL)-6 and C-reactive protein.…”
Section: Introductionmentioning
confidence: 99%